PENGARUH MANAJEMEN RANTAI PASOKAN SISTEM ERP DALAM MENINGKATKAN KINERJA PERUSAHAAN STUDI KASUS: PT LATINUSA TBK - Ivan Jones; Lusiana Lusiana; Moderin Moderin; Fenny Fenny (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
It can be said that the existence of an ERP system in a company that is done well is a very important aspect. In this research, the researcher wants to know how far later the ERP aspect affects supply chain management that occurs at PT. Latinusa Tbk. From the results of the research that has been done, it is concluded that the implementation of a good ERP process at PT. Latinusa Tbk has a good significant influence on the performance of SCM which is owned by PT. Latinusa Tbk in the future